Analisis Perilaku Siswa Dalam Menjaga Kebersihan Lingkungan di Sekolah SMP Negeri 7 Kota Ternate - Rosalinda Hartono; Yumima Sinyo; Jailan Sahil (FKIP Universitas Khairun, 2025)
Clean and healthy living behaviour is a manifestation of the reality of human life by applying learning principles to students to behave to love the school environment. The state of the environment is closely related to the process of changing student behaviour for the better. The purpose of this study was to analyse the level of student behaviour towards environmental cleanliness at SMP Negeri 7 Ternate City. The research method uses a quantitative descriptive approach, which describes data made either alone or in groups. Using data from 60 respondents from all students at SMP N 7 Ternate City, totalling 1,110 students. The technique in sampling uses simple random sampling, namely as a simple random sample without regard to strata in the population. The results showed that students' behaviour in maintaining environmental cleanliness at SMP Negeri 7 Ternate City was obtained a percentage value of 84.00% with a very caring category based on three indicators, namely: 1) indicators of always maintaining cleanliness and environmental sustainability; 2) loving the tidiness of the classroom and; 3) participant-based environmental activities